Legal political reconstruction is progressive responsive as a regulation reform effort to realize state goals - Donny Eddy Sam Karauwan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Legal politics is a basic guideline in the process of determining values, establishing and shaping legal development in Indonesia. Legal development aims to establish an Indonesian national legal system that reflects the ideals, soul, spirit and social values that live in Indonesia. This study discusses legal politics in relation to legal development through a progressive legal approach that is certain to be able to realize the goals of the state. This study uses a normative method with a descriptive analysis approach, concluding that the reconstruction of legal politics is sought to reform regulations in a better direction and by building legal politics that is characterized by progressive responsiveness, it can realize state goals that are devoted to justice and welfare